PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR - Winata, Liana Angelina; Angeline, Patricia -; Putri, Viona -; Meiden, Carmel - (Makro Jurnal Manajemen Dan Kewirausahaan, 2023)
One of the main concerns of corporate financial management is how managers make short-term decisions known as working capital management. This requires making capital management policies and decisions that have an impact on performance. The purpose of this study is to find out how the literature on the impact of working capital management on company profitability has changed over time. Publish or Perish, a software program, was used to conduct research in 25 journals from 2012 to 2022 using a systematic literature review technique. The results of this study suggest that increasing working capital will increase profitability when working capital levels are low. However, profitability will decrease as working capital increases when the working capital level is high. In addition, reliable estimates of a company's ideal NTC level are provided in this report. Furthermore, this investigation examines the impact of financial constraints on the ideal level of working capital. The results of this literature review show that working capital management has an effect on company profitability.